The impact of financial performance of food and beverage companies listed in Bursa Malaysia during the old SST and GST period / Nuramirah Syafiqah Ramlan - Ramlan, Nuramirah Syafiqah (2019)
The motive for this paper is to discover the impacts of financial performance of food and beverage companies listed in Bursa Malaysia during the old SST and GST period. This research is based on four independent variables that were empirically examined for their relationship with financial performance (ROE). These variables are: working capital (WC), company’s efficiency (ATR), liquidity (LQ) and leverage (LEV). Data of 30 companies of food and beverage companies listed on Bursa Malaysia covering the period from 2012 to 2014 (SST period) and 2015 to 2017 (GST period) were extracted from companies’ annual reports. Random-effects were used to analyse the data. Based on the regression result, during the SST period the findings showed a positively significant relationship between company’s efficiency (ATR) towards financial performance meanwhile working capital (WC), liquidity (LQ) and financial leverage (LEV) have negative and insignificant effect towards financial performance. Meanwhile during GST period, it was found that company’s efficiency (ATR) and financial leverage (LEV) have significant and positive effect towards financial performance (ROE). However, working capital (WC) and liquidity (LQ) has negative and insignificant effect towards financial performance (ROE). This study differs than previous studies as it is covers period with two different tax regimes which are SST and GST.